Leadership and the power of resentment/ressentiment. (February 2020) - Ciulla, Joanne B
This paper examines the emotion of resentment and the French version of it, ressentiment . It shows why resentment is an effective way for leaders to cultivate followers who are loyal to them even when they do not serve the followers' interests. I begin by looking at the differences between the two concepts of resentment and ressentiment in the literature and how they relate to justice, fairness, self-esteem, social status, nostalgia, and other emotions. Next, I go on to explore one of the most harmful aspects of resentment, the social and moral bi-product of it that Nietzsche and Scheler call the "inversion of values." This is when leaders convince followers that what is considered good by those they resent as bad, and vice versa. I then construct a picture of how leaders like Donald Trump cultivate resentment and invert values. While I do not offer a panacea for resentment, I believe that understanding it better may point us towards a cure.